THE FEELING UNDERSTANDING AND VALUES OF THE DEAF CHILDREN - Qurrata 'Ain; Margana Margana (Lire Journal (Journal of Linguistics and Literature), 2019)
Deaf children have a language to communicate with each other. It is known as sign language. The sign language has grammatical, morpheme, syntactical and semantically rules. It can be helped the deaf children to understand the signs. The disability people or gift children have an equal with normal people. So, they deserve to get what they want and communicate with each other. Generally, the grammar of sign language for deaf people has used hand shape or movement even facial expression or body movement. This article has aimed to expose the ability of deaf children to understand the feelings and values of others. It refers to social and cognitive development. Deaf children have access to communicate how peoples’ interaction and explanation for behaviors to get better social dynamics as an advantage in cognitive development. The deaf children often show the behavior problem and inconsistent social and sometimes they could not understand social rules.